Elevated ASCL2 expression is associated with metastasis of osteosarcoma and predicts poor prognosis of the patients - Liu, Ming-Han (Am J Cancer Res, 2016)
Achaetescute-like 2 (ASCL2), a basic helix-loop-helix (bHLH) transcription factor, plays an important role in the determination of neuronal precursors in the central and peripheral nervous system and involves in tumor progression. However, the role of ASCL2 expression in the osteosarcoma prognosis has not been elaborated. This study aimed to evaluate ASCL2 expression level in osteosarcoma and assess its prognostic value for patients. ASCL2 protein expression was detected by immunohistochemistry (IHC) in 73 cases of osteosarcoma. Kaplan-Meier analysis and Cox regression analysis were performed to evaluate the prognostic significance of ASCL2. Immunohistochemistry analysis showed that the overall survival and metastasis-free survival of patients with positive ASCL2 expression were significantly shorter than patients with negative expression (both P<0.01). Multivariate Cox analysis identified ASCL2 expression as an independent prognostic factor to predict poor overall survival and metastasis-free survival (both P<0.01). Overexpression of ASCL2 expression greatly promoted cell proliferation and enhanced migration and invasion in vitro. This study indicates that increased expression of ASCL2 in primary osteosarcoma is a novel biomarker for predicting the development of metastases and poor outcomes of the patients.